The mathematician's mind : the psychology of invention in the mathematical field - Hadamard, Jacques, 1865-1963. (Princeton, N.J. : Princeton University Press, 1996)
Fifty years ago when Jacques Hadamard set out to explore how mathematicians invent new ideas, he considered the creative experiences of some of the greatest thinkers of his generation, such as George Polya, Claude Levi-Strauss, and Albert Einstein. It appeared that inspiration could strike anytime, particularly after an individual had worked hard on a problem for days and then turned attention to another activity. In exploring this phenomenon, Hadamard produced one of the most famous and cogent cases for the existence of unconscious mental processes in mathematical invention and other forms of creativity.
General views and inquiries -- Discussions on unconsciousness -- The unconscious and discovery -- The preparation stage. Logic and chance -- The later conscious work -- Discovery as a synthesis. The help of signs -- Different kinds of mathematical minds -- Paradoxical cases of intuition -- The general direction of research.
Originally published: An essay on the psychology of invention in the mathematical field. Princeton : Princeton University Press, 1945.
Includes bibliographical references.
Print version record.
IEEE
Keywords: Mathematics -- Philosophy; Mathematicians -- Psychology; x; x; MATHEMATICS -- History & Philosophy; Mathematicians -- Psychology; Mathematics -- Philosophy; 2; Mathematiker; Psychologie; Electronic books